User Experience Analysis on Bakamla Messenger Applications Using User Experiences Questionnaire (UEQ) - Hozairi; Buhari; Rofiudin; Syariful Alim (IAIC Publishing, 2023)
User experience describes the experience a user gets when using a software product. This research aims to measure the user experience when using the Bakamla Messenger application. Measurements were carried out using the User Experience Questionnaire (UEQ) method. The research was carried out by distributing online questionnaires to users of the Bakamla Messenger application, with a total of 117 respondents. The measurement results for the attractiveness aspect of 2.26, clarity of 2.30, efficiency of 2.24, accuracy of 2.27, and stimulation of 2.28 have a positive impression value and are included in the excellent criteria. However, the novelty aspect gets a value of 0.02, meaning it has a negative impression value and is included in the bad criteria, so the innovation of the product needs to be increased. Thus, we recommend that Bakamla messenger application developers focus on improving aspects of the novelty value of the application, such as the level of security of confidential data and the messenger system being able to provide new features beyond messenger in general.